ANALISIS KOMPARATIF SMART FARMING DAN PERTANIAN TRADISIONAL BERBASIS TEKNIK INDUSTRI - Nurhayati, Ai; Saepudin , Saepudin; Rivai , Ahmad (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This study examines the comparative analysis between smart farming and traditional farming, focusing on efficiency, productivity, and sustainability from the perspective of Industrial Engineering. The main issues addressed include the challenges of conventional agricultural methods in Indonesia, such as low productivity, high resource consumption, and vulnerability to climate change. The research aims to evaluate the advantages and limitations of both systems, highlighting how digital technologies and automation can optimize agricultural processes. The methodology employed is a qualitative comparative literature review, drawing data from international and national journals, textbooks, and reports by institutions such as FAO and the World Bank. The findings indicate that smart farming significantly enhances productivity, resource efficiency, and environmental sustainability, whereas traditional farming remains relevant due to low cost and cultural alignment but suffers from inefficiency and a higher risk of crop failure. Integrating smart farming technologies with local knowledge can create a more sustainable and resilient agricultural system.